2008
DOI: 10.1038/ismej.2008.78
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic diversification of Pseudanabaena spp. (cyanobacteria)

Abstract: Pseudanabaena species are poorly known filamentous bloom-forming cyanobacteria closely related to Limnothrix. We isolated 28 Pseudanabaena strains from the Baltic Sea (BS) and the Albufera de Valencia (AV; Spain). By combining phenotypic and genotypic approaches, the phylogeny, diversity and evolutionary diversification of these isolates were explored. Analysis of the in vivo absorption spectra of the Pseudanabaena strains revealed two coexisting pigmentation phenotypes: (i) phycocyanin-rich (PC-rich) strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 71 publications
3
52
0
Order By: Relevance
“…We speculate that the divergence of niches, such as substance utilization and adaptation to environmental conditions (Macalady et al, 2008), could allow for this situation. Generally, genotypic diversification (Schauer et al, 2005) and even only phenotypic diversification (Acinas et al, 2009) can lead to bacterial niche divergence. Our phylogenetic analysis showed that genetic polymorphisms were evident among the Clostridium sequences, in which eight new clusters and subclusters (CLOS.1-8) and 18 singletons could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the divergence of niches, such as substance utilization and adaptation to environmental conditions (Macalady et al, 2008), could allow for this situation. Generally, genotypic diversification (Schauer et al, 2005) and even only phenotypic diversification (Acinas et al, 2009) can lead to bacterial niche divergence. Our phylogenetic analysis showed that genetic polymorphisms were evident among the Clostridium sequences, in which eight new clusters and subclusters (CLOS.1-8) and 18 singletons could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the central part of the Lake Maggiore, two specimens revealed the presence of several cyanobacteria mostly belonging to Oscillatoriales. The blooms were mainly due to Pseudanabaena spp., an unusual condition in Lake Maggiore, as this taxon commonly blooms in eutrophic water bodies (Mayer et al, 1997;Zwart et al, 2005); nonetheless, its characteristics are poorly investigated (Acinias et al, 2009) even widely distributed as it occurs in diverse aquatic as well as in benthic environments (Castenholz et al, 2001;Zwart et al, 2005;Diez et al, 2007). In the two samples collected in the central lake station, several species belonging to Oscillatoriales have contributed to the algal bloom, among which Pseudanabaena dominated, both in terms of density (68.6 and 57.0%, respectively) and biomass (47.2 and 52.6%).…”
Section: Bloom Maps and In Situ Analysismentioning
confidence: 99%
“…, 12 days, n = 3): a variation of cell density; b variation of total 2-MIB; c variations of extracellular, dissolved intracellular, and bound intracellular 2-MIB; d variation of total 2-MIB/cell density value Discussion Identification of Pseudanabaena Pseudanabaena has drawn little attention in the scientific community where limited data exist about their phenotypic and genetic characteristics (Acinas et al 2009). Pseudanabaena species are nonheterocystous cyanobacteria belonging to the order Oscillatoriales.…”
Section: -Methylisoborneol Production Under Different Light Intensitiesmentioning
confidence: 99%